(untitled) (Community Based Medical Journal, 2016)
A cross-sectional study was carried out for a period of six months in the outpatient Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Ninety three patients having acne vulgaris were selected. The study showed that the mean age of the cases was 20.7 with standard deviation 5.4 years. Highest percentage of patients was unmarried among the cases (79.6%) and proportion of higher secondary education (63.4%) was found to be high among the cases. The study showed that proportion of student (75.3%) and housewife (12.9%) were found to be high among the cases. All the patients had presented with comedones (blackheads and whiteheads). All the patients had acne in the face and it was found that 78.5% had papules, 17.2% had pustules & 4.3% had nodules. 90.3% patients presented with multiple lesions. 95.7% lesions are on check. Considering the pattern of treatment received, 28% of the patients mentioned that they used topical steroid, 19.6% had received retinoids and 28% had received antibiotics. To get an overall impression of the country regarding acne vulgaris, more integrated study is needed. This was a study on a limited number of cases. Future studies must include economical support, then large sample size could be ensured and study finding would be more reliable. There is a great need of epidemiological studies also, with sufficient follow-up, systematic reviews and meta-analyses on this issue. CBMJ 2016 July: Vol. 05 No. 02 P: 33-38